Quasi-Fiscal Deficit in Non-Financial Enterprises - Tchaidze, Robert (IMF Working Papers; Working Paper ;, 2007)
This paper discusses two ways of evaluating the quasi-fiscal deficit (QFD) and the link between them. It also suggests how to properly account for the QFD when calculating the overall deficit of the public sector. Finally, using an example of the energy market, it shows how to untangle a web of mutual nonpayments and properly evaluate the QFD generated in a sector characterized by the presence of both private and public agents.